Case report: Fatal traumatic coronary artery dissection—an overlooked complication of chest fracture - Jiang, Tao; Qian, Cheng; Wei, Gang; Cheng, Ling; Zheng, Wenwu; Chen, Gong (Frontiers in Cardiovascular Medicine, 2023)
Coronary artery dissection caused by trauma is a rare occurrence that can be life-threatening. Accordingly, its rapid identification and treatment are essential to improve patient outcomes. Here, we present a case of a patient who suffered multiple rib and femur fractures after falling from a height of eighteen meters and subsequently experienced persistent chest pain. After the initial diagnostic workup, the medical team diagnosed the patient's chest pain as rib fractures and failed to consider the potential of a cardiac injury as the underlying cause. No emphasis was placed on monitoring changes in myocardial enzymes and ECG, which could have indicated coronary artery dissection. The dissection was confirmed and treated with a stent only after the subsequent coronary angiography (CAG) and optical coherence tomography (OCT) examinations, gradually relieving the patient's chest pain. In this case report, we discuss the management of fractures complicated by traumatic coronary artery dissection and highlight the benefits of OCT in diagnosing and treating this condition. The case also emphasizes the importance of considering coronary artery injury in patients with chest pain due to trauma.